The effects of testosterone on ventilatory responses in men with obstructive sleep apnea: a randomised, placebo‐controlled trial. (19th January 2013) - Killick, Roo; Wang, David; Hoyos, Camilla M.; Yee, Brendon J.; Grunstein, Ronald R.; Liu, Peter Y.
Summary We recently showed that testosterone therapy worsens sleep‐disordered breathing at 6–7 weeks, but not after 18 weeks, in men with obstructive sleep apnea. Changes in ventilatory chemoreflexes may be responsible. The effect of testosterone on ventilatory chemoreflexes in men with obstructive sleep apnea has not been systematically studied before. Twenty‐one obese men with obstructive sleep apnea, a subgroup of our recent report, were randomised in an 18‐week, randomised, double‐blind, placebo‐controlled, parallel group trial to three intramuscular injections (0, 6, 12 weeks) of either 1000 mg testosterone undecanoate (n = 10) or placebo (n = 11). Awake ventilatory chemoreflex testing was performed before (week 0), during (week 6) and at the end of treatment (week 18) to determine the ventilatory carbon dioxide recruitment threshold and chemosensitivity. Sleep and breathing was assessed by overnight polysomnography at 0, 7 and 18 weeks. Serum hormones levels were measured at every visit. A significant increase in blood testosterone levels (5.65 nmol L−1, 0.51–10.8 nmol L−1, P = 0.03) and lean muscle mass (2.36 kg, 0.8–3.9 kg, P = 0.007) between the two groups was observed as expected. No significant differences were seen in ventilatory chemoreflexes between the two groups at 6 weeks or at 18 weeks. However, positive correlations were observed between changes in serum testosterone and hyperoxic ventilatory recruitment threshold (r = 0.55, P = 0.03), and between changes in hyperoxic ventilatory recruitment threshold and time spent with oxygen saturations during sleep <90% (r = 0.57, P = 0.03) at 6–7 weeks, but not at 18 weeks. Time‐dependent alterations in ventilatory recruitment threshold may therefore mediate the time‐dependent changes in sleep breathing observed with testosterone.